Historians and nationalism East-Central Europe in the nineteenth century - Baar, Monika (Oxford historical monographs., 2010)
Monika Baar examines the work of five prominent East-Central European historians in the 19th century, analyzing and contrasting their body of work, their promotion of a national culture, and the contributions they made to European historiography.